„Ukraine is above all else“ or „Pushkin is our everything“? (Ukrainian education and Russian literature) - Kovbasenko, Y. (Studia Philologica, 2022)
The paper investigates three types of war hybridly imposed on Ukraine by Russia, namely «War of Ares» «War of Athena» and «War of Apollo» as well as the reasons, process and results of using the culture and literature as a brilliant veil to mask the imperial essence, «crooked mug of Russia» (M. Gogol). The author analyzes why, despite full-scale Russian military aggression against Ukraine waged on February, 24, 2022 and also shocking war crimes of the rashists, the piety to Russia and its «great» culture and literature has still been remained in a wide circle of the world community and even Ukrainian society. The conclusion is drawn that deadly (like «Snow White’s apple») combination of aesthetic appeal, on the one hand, and imperial ideological toxicity, on the other hand (especially in the conditions of full-scale Russian military aggression when even the language in which the mentioned works were written has become a trigger for millions of Ukrainians), makes Russian literature absolutely unacceptable for studying in Ukrainian secondary educational institutions. The origins and stages of rooting the myth about the «world greatness» of Russian literature are observed, and the reasonable conclusion is drawn that the significant number of Russian works in our school programs is not an evidence of their supposed «world» ideological and aesthetic level, but severe heritage of the imperial (including Soviet) epoch when in lands colonized by Muscovy (in particular, in Ukraine) there was forced assimilation (russification) of the population, so all Russian was imposed by force. The effective ways of updating the strategies of studying Russian literature in Ukrainian higher educational institutions are predicted, for example, intensive use of postcolonial interpretation and comparative analysis, updating and / or expanding the range of studied literary works and using new approaches to study the writer’s biographies. It is claimed that a strategic turn in teaching Russian literature and culture in Ukrainian higher educational institutions will require not only titanic efforts of educators but also the whole state, the development and implementation of a strategic target government program. Keywords: „war of Apollo“, hybrid warfare, glorification of the imperial literary canon, imperial myth, national identity, postcolonial studies, „raschism“, semantic (paradigmatic) war, „troubadours of the Empire“.